Development of professional identity among dental students – A qualitative study. Issue 1 (2nd September 2022) - Du, Xiangyun; Al Khabuli, Jumma O. S.; Ba Hattab, Raidan A. S.; Daud, Aala; Philip, Nebu I; Anweigi, Lamyia; Matoug‐Elwerfelli, Manal; Ali, Kamran
Abstract: Purpose: The study explored dental students' perception of their professional identity (PI) development at a newly established dental college with a problem‐based learning (PBL) curriculum. Methods: Qualitative methods based on focus groups were used for data collection. The conceptual framework of the study was informed by a subject‐centered sociocultural approach to PI development. Purposive sampling was used to collect data from five focus groups of undergraduate dental students to gain a deeper understanding of their PI development in a PBL environment. Results: Out of a total of 38 dental students in years 2 and 3, 34 students (89.47%) participated in the focus groups. A theory‐driven thematic analysis was used to dissect the views and experiences of the participants to explore factors contributing to PI development in the early years of the program. At an individual level, PBL was seen to be appropriate for PI development. However, some participants placed more emphasis on practical training in operative dental skills. Relational sources especially role modeling by the PBL facilitators and faculty staff were identified as a key factor to nurture PI development. Mixed views were observed on the value of PBL to enhance team‐working skills. The participants also identified challenges of PBL and provided recommendations on further improvements to enhance the learning experiences of the students. Conclusions: This study provided useful insights into a PBL curriculum at a newly established dental institution. The findings underscore the value of PBL in developing PI and also highlight the challenges of implementing PBL in a socio‐cultural context and pedagogical implications for further program improvement.